2016
DOI: 10.1038/bonekey.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Role of milk fat globule-epidermal growth factor 8 in osteoimmunology

Abstract: Milk fat globule-epidermal growth factor 8 (MFG-E8) is a glycoprotein that is abundantly expressed in various tissues and has a pivotal role in the phagocytic clearance of apoptotic cells. However, MFG-E8 has also gained significant attention because of its wide range of functions in autoimmunity, inflammation and tissue homeostasis. More recently, MFG-E8 has been identified as a critical regulator of bone homeostasis, being expressed in both, osteoblasts and osteoclasts. In addition, it was shown that MFG-E8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Wang et al ( 47 ) suggested that APOC3 may be a prognostic biomarker for hepatocellular carcinoma (HCC). Milk fat globule-epidermal growth factor 8 (MFGE8) is a lipophilic glycoprotein that is widely involved in cell interactions and plays an important role in inflammatory injury, fibrosis, tumor development, and other diseases ( 48 ). Tian et al ( 49 ) highlighted that MFGE8, as a COX-2-related gene, is involved in the regulation of tumor lung colonization in triple negative breast cancer (TNBC), and that silencing MFGE8 expression in TNBC cells significantly restored sensitivity to selective inhibitors of COX-2 both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 47 ) suggested that APOC3 may be a prognostic biomarker for hepatocellular carcinoma (HCC). Milk fat globule-epidermal growth factor 8 (MFGE8) is a lipophilic glycoprotein that is widely involved in cell interactions and plays an important role in inflammatory injury, fibrosis, tumor development, and other diseases ( 48 ). Tian et al ( 49 ) highlighted that MFGE8, as a COX-2-related gene, is involved in the regulation of tumor lung colonization in triple negative breast cancer (TNBC), and that silencing MFGE8 expression in TNBC cells significantly restored sensitivity to selective inhibitors of COX-2 both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that MFG-E8 plays an important role in the balance of bone metabolism, especially under pathological conditions. 10 Moreover, patients with rheumatoid arthritis reportedly have lower serum concentrations of MFG-E8 than do healthy controls, and MFG-E8 deficiency augments the severity of arthritis in mice. 11 Similar to previous findings, the present study demonstrated that the plasma MFG-E8 level was lower in patients with than without knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…9 A previous study showed that MFG-E8 plays an important role in the balance of bone metabolism, especially under pathological conditions. 10 Patients with rheumatoid arthritis have a lower serum concentration of MFG-E8 than do healthy controls, and MFG-E8 deficiency augments the severity of arthritis in mice. 11 Moreover, the involvement of proinflammatory cytokines and chronic inflammatory processes in the pathophysiology of OA is generally accepted.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 MFG-E8-deficient mice exhibited increased RANKL-induced osteoclastogenesis ex vivo. 22,23 Sinningen et al also reported that MFG-E8-deficient mice exhibited impaired bone formation and mineralization compared with wildtype animals. 24 It is vital to promote the recruitment of BMSCs in the microenvironment surrounding a fracture hematoma and to induce osteogenic differentiation of MSCs to facilitate bone healing.…”
Section: Introductionmentioning
confidence: 98%